2014
DOI: 10.1021/la404693s
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Suspensions Containing Carbon Blacks Used as Conductive Additives in Composite Electrodes for Lithium Batteries

Abstract: International audienceSuspensions of carbon blacks and spherical carbon particles are studied experimentally and numerically to understand the role of the particle shape on the tendency to percolation. Two commercial carbon blacks and one lab-synthesized spherical carbon are used. The percolation thresholds in suspensions are experimentally determined by two complementary methods: impedance spectroscopy and rheology. Brownian dynamics simulations are performed to explain the experimental results taking into ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…These interactions represent the friction exerted by the fluid on the colloid that is moving and the collisions between solvent molecules and the colloid, respectively. According to our previous study, 31 which has shown the importance of taking into account the shape of carbon additives, carbon black aggregates are modeled as nondeformable fractal-like aggregates composed of small spheres (elementary particles) linked together. Each carbon black aggregate move indeed as a single entity in the simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions represent the friction exerted by the fluid on the colloid that is moving and the collisions between solvent molecules and the colloid, respectively. According to our previous study, 31 which has shown the importance of taking into account the shape of carbon additives, carbon black aggregates are modeled as nondeformable fractal-like aggregates composed of small spheres (elementary particles) linked together. Each carbon black aggregate move indeed as a single entity in the simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we have shown that it is possible to consider the real shape of carbon black aggregates in the framework of Brownian dynamics simulations. 31 In Ref. 31 we have indeed studied both experimentally and numerically colloidal suspensions only composed of carbon particles (carbon black aggregates or spherical carbon particles).…”
mentioning
confidence: 99%
“…Recent studies from the authors' research group have demonstrated the impact of solvent evaporation rate on the favorable aggregation of conductive additives via mesoscale computational modeling, however requiring experimental understanding of the role of evaporation in the drying step on the electrode microstructure and performance. 29,30 There are a handful of other recent studies employing particle based simulations [31][32][33][34][35] which are farther away from typical electrode preparation and include rather restrictive physical assumptions and/or property values. Figure 1 schematically demonstrates the stages during drying of a typical electrode slurry cast on a substrate (current collector).…”
mentioning
confidence: 99%
“…Both factors can in principle alter the value of / c . Previous simulations of carbon blacks aggregates have shown that a high colloid anisotropy decreases / c [37]. However, since anisotropy is much weaker in the case of alumina, / c is expected to be essentially unaffected by it.…”
Section: Resultsmentioning
confidence: 90%